IMPLIKASI EFISIENSI MODAL KERJA, LIKUIDITAS, DAN SOLVABILITAS TERHADAP PROFITABILITAS - Mulyana, Bambang; Elisabeth, Ermy (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2018)
This research aims to know and to analyze the influence of the efficiency of working capital, liquidity and solvency toward company’s profitability. The Object for this research is financial statements of a national general insurance company, PT. Berdikari Insurance, that located in Jakarta. This research was done toward quarterly’s financial statement that regularly submitted to Otoritas Jasa Keuangan  from year 2010 until 2014 by using associative approach. Thus, data analysis which is used is statistic analysis in the form of multiple linear regression test. The result of this research shows that simultaneously  the variable of the efficiency of working capital, liquidity and solvency influence to profitability for Net Profit Margin and Return On Equity. Meanwhile, all independend variables are not influence to profitability for Return On Investment.  Partially,  solvency influence to profitability for Net Profit Margin. The variable of the effiency of working capital and solvency influence to profitability for Return On Equity.  It has been proven from the result of (F) simultant test and the result of (t) partial shows significant point of the three independend variables that support the hipothesys. Therefore, the accepted assumptions are, (1) there is influence between the efficiency of working capital, liquidity and solvency toward Net Profit Margin (2) there is no influence between the efficiency of working capital, liquidity and solvency toward Return On Investment (3) there is influence between the efficiency of working capital, liquidity and solvency toward Return On Equity.